2017
DOI: 10.3389/fnagi.2017.00274
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stress-Diathesis Model to Predict Risk of Post-operative Delirium: Implications for Intra-operative Management

Abstract: Introduction: Risk assessment for post-operative delirium (POD) is poorly developed. Improved metrics could greatly facilitate peri-operative care as costs associated with POD are staggering. In this preliminary study, we develop a novel stress-diathesis model based on comprehensive pre-operative psychiatric and neuropsychological testing, a blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) carbon dioxide (CO2) stress test, and high fidelity measures of intra-operative parameters that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…It was indicated that patients undergoing MIS suffered a less incidence of POD and lower inflammatory markers compared with those with open surgeries, consistent with a lower degree of stress response (Tan et al, ). However, recent work suggested that intraoperative CO 2 control may be an independent marker of POD risk (El‐Gabalawy et al, ; Mutch & El‐Gabalawy, ). Previous studies revealed that mild hypercapnia and substantial vasodilation in the brain induced during MIS resulted in alterations in cerebrovascular reactivity to a CO 2 stress in patients that may be used to identify patients at cognitive risk (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that patients undergoing MIS suffered a less incidence of POD and lower inflammatory markers compared with those with open surgeries, consistent with a lower degree of stress response (Tan et al, ). However, recent work suggested that intraoperative CO 2 control may be an independent marker of POD risk (El‐Gabalawy et al, ; Mutch & El‐Gabalawy, ). Previous studies revealed that mild hypercapnia and substantial vasodilation in the brain induced during MIS resulted in alterations in cerebrovascular reactivity to a CO 2 stress in patients that may be used to identify patients at cognitive risk (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This signal has previously been identified as a biomarker for POND in these patients after surgery. 23 As such, examination of the potential consequences of alterations in CVR to respiratory gases during anaesthesia and surgery appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative considerations include neuroinflammatory effects consequent with surgical stress 181920 , and premorbid risk factors (e.g., cognitive dysfunction, psychiatric illness, increasing age) which may influence the incidence of POND. 32122 More recent work suggests that a multi-factorial approach, described as a stress-diathesis model 23 , may provide further insights. In this model, the conduct of anaesthesia, which includes the management of respiratory gases during mechanical ventilation, may contribute to the stress of the perioperative period in vulnerable individuals (the diathesis) and is associated with development of POND.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings from the adult literature regarding postoperative delirium (POD) and cognitive dysfunction in the elderly, also considered to reflect potential anesthetic neurotoxicity, may help in this regard. El‐Gabalawy et al have proposed a stress‐diathesis model to investigate the phenomenon. In preliminary work, an underlying propensity or diathesis, determined by preoperative neurocognitive testing and/or MRI imaging, coupled with a stress—anesthesia and surgery—is more predictive of postoperative delirium than anesthetic duration per se.…”
mentioning
confidence: 99%